A case of Glanzmann's Thrombasthenia - Diagnosed During Evaluation of Post-Surgery Bleeding. - Akter, Mafruha; Khalil, Mohammad Ibrahim; Koron, Tahmid E Rabbani Khairul; Saleh, Abu Zaffor Md; Faruk, Imtiaz (Journal of Surgical Sciences, 2021)
Glanzmann’s thrombasthenia (GT) is a very rare inherited autosomal recessive bleeding disorder due to platelet dysfunction. Clinical presentations and severity of bleeding are heterogeneous. Bleeding pattern is usually muco-cutaneous ranging from mild bruising to potentially life threatening bleeding, although severe internal organ bleeding is rare except in trauma or post surgery without precaution. Genetic defect of GT is associated with mutations in gene encoding platelet membrane glycoprotein GPIIb/IIIA leading to lack of platelet aggregation due to reduced expression or complete absence of GPIIb/IIIA. Here we report a case of GT who was diagnosed first time at 20 years of age after emergency surgery without proper evaluation and precaution in a resource limited situation. However she was managed by platelet transfusion and antifibrinolytic therapy. Journal of Surgical Sciences (2021) Vol. 25(2) : 47-51